0913 Nocturia Improves Among Women Treated With Behavioral Therapy For Insomnia. (27th April 2018) - Fung, C H; Alessi, C; Mitchell, M N; Vaughan, E C; Huang, A J; Markland, A D; Mc Gowan, S; Lee, D; Song, Y; Jouldjian, S; Josephson, K; Martin, J L
Abstract: Introduction: Nocturia is common among women and is associated with worse quality of life and work absenteeism. Treatments include behavioral therapies (e.g., urge suppression) and medications. Bothersome nocturia may persist despite these treatments, and some patients are unable to tolerate treatment, suggesting a need for additional strategies. Nocturia and insomnia are interrelated, but few studies have examined the impact of behavioral therapy for insomnia on nocturia symptoms. We examined predictors of nocturia in women with insomnia disorder and assessed for changes in nocturia associated with behavioral intervention for insomnia. Methods: In an ongoing comparative effectiveness trial (cognitive behavioral therapy for insomnia versus acceptance and commitment therapy for insomnia) conducted at a VA medical center among women with chronic insomnia disorder, self-reported nocturia data (i.e., frequency of nocturia in past month; 0–5+/night) were collected at baseline, post-intervention, and 3-month follow-up and categorized as presence/absence of clinically-relevant nocturia (≥2 versus < 2 times/night); cut point based on epidemiological evidence and expert opinion. In a logistic regression model, the relationship between baseline nocturia and age, apnea-hypopnea index (AHI), and Patient Health Questionnaire-9 item (PHQ-9; depression) was examined. An exact McNemar's test for paired binomial data was used to examine changes in the proportion of women (in both treatment groups combined) with nocturia post-treatment and at 3-months follow-up. Results: Among trial participants (N=149, mean age 48.0, SD=13.2; 23–91 years), clinically-relevant nocturia was present in 38.9% at baseline and was associated with older age (adjusted odds ratio [OR] 1.05; 95% CI: 1.02, 1.09), but not AHI or PHQ-9 (p values >.085). Behavioral intervention for insomnia was associated with a reduction in the proportion of women with clinically-relevant nocturia post-treatment (20.6%) compared to baseline (N=141; McNemar's X 2 =16.95, OR 0.23, p<.001) and at 3-months follow-up (15.4%) compare to baseline (N=116; McNemar's X 2, OR 0.19, p<.001). Conclusion: Behavioral therapy for insomnia in women is associated with reduced nocturia. Future studies should examine the efficacy of behavioral therapy for insomnia provided alone or in combination with other treatments for improving nocturia symptoms in women. Support (If Any): VAHSRDIIR13058, K23AG045937.